Electrochemical Remediation: Molecular Tuning of Redox‐Copolymers for Selective Electrochemical Remediation (Adv. Funct. Mater. 52/2020). (22nd December 2020) - Kim, Kwiyong; Baldaguez Medina, Paola; Elbert, Johannes; Kayiwa, Emmanuel; Cusick, Roland D.; Men, Yujie; Su, Xiao
Abstract : In article number 2004635, Xiao Su and co‐workers report the molecular design of redox copolymers with tunable affinity, redox activity, and hydrophobicity for the electrochemical separation of organic pollutants, including highly persistent contaminants such as perfluoroalkyl substances. The proposed strategy highlights new directions in the rational design of electroactive polymers for next‐generation water purification and environmental remediation.